Managing Utah's water through interbasin transfer - Dimick, Franklin E., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
In order to utilize and manage the portion of Colorado River Water allotted to the State of Utah to the fullest extent, a significant problem has to be overcome. Approximately 80% of the population of Utah lives along the Wasatch Front between Ogden and Provo in the Bonneville Basin. The area in the eastern part of the state that is in the Colorado River Drainage Basin is very sparsely populated and has relatively little irrigable land. This means that in order to maximize the use of this water, it must be transferred between basins. The Bureau of Reclamation planned, designed and is constructing the Central Utah Project to achieve this interbasin transfer. The purpose of this project is to divert water from streams that are tributary to the Colorado River and transport it to the Bonneville Basin where the major population centers and the prime irrigab1e lands are located. The major features of the Project used for the interbasin transfer are the Strawberry Aqueduct, three storage reservoirs (one with a capacity of over one million acre-feet), and seven diversions structures of various capacities. Additional storage reservoirs have also been built downstream of the aqueduct to capture and store excess runoff to minimize the impacts created by diverting the water. Proper operation and management of this system will result in the interbasin transfer of 142,500 acre-feet of water annually, in addition to the 56,700 acre-feet diverted for the Strawberry Project, thus utilizing a portion of Utah's Colorado River water.
USCID regional meetings -- 1989
Interbasin transfer
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.